2013
DOI: 10.5194/acp-13-4577-2013
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol composition, sources and processes during wintertime in Beijing, China

Abstract: Air pollution is a major environmental concern during all seasons in the megacity of Beijing, China. Here we present the results from a winter study that was conducted from 21 November 2011 to 20 January 2012 with an Aerodyne Aerosol Chemical Speciation Monitor (ACSM) and various collocated instruments. The non-refractory submicron aerosol (NR-PM1) species vary dramatically with clean periods and pollution episodes alternating frequently. Compared to summer, wintertime submicron aerosols show much e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

112
396
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(518 citation statements)
references
References 68 publications
112
396
9
1
Order By: Relevance
“…2A). Hence, SO 4 2− and NO 3 − in fine PM are completely neutralized, because of the presence of high levels of gaseous ammonia (17)(18)(19)(20)(21)(22)(23) , and Cl − ) is also near unity (Fig. 2B and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). Hence, SO 4 2− and NO 3 − in fine PM are completely neutralized, because of the presence of high levels of gaseous ammonia (17)(18)(19)(20)(21)(22)(23) , and Cl − ) is also near unity (Fig. 2B and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the acidity, hygroscopicity, and RH represent the key factors for sulfate formation on fine PM, explaining the differences in the various ambient measurements (14,(20)(21)(22)(23)(24)(25). For example, the acidity effect on fine aerosols is effectively overcome by NH 3 neutralization in Xi'an and Beijing (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed descriptions of ACSM measurements can be found in Sun et al [2012Sun et al [ , 2013. In addition, all the data in this study are reported at Beijing local time which equals Coordinated Universal Time (UTC) plus 8 h.…”
Section: Instrument Operationsmentioning
confidence: 99%
“…Large plenty of researches have been conducted for the purpose of understanding the size distribution and components [7,8] , optical characteristics [9,10] , and physicochemical properties of aerosol particles [2,11] . The transportation and diffusion of aerosol is vital for the prediction of affected area and the exploration of the emission source.…”
Section: Introductionmentioning
confidence: 99%